A STUDY ON EVALUATING DETERMINANTS OF JOB SATISFACTION OF STOCK BROKERS MUMBAI REGION (International Journal of Engineering Management Science, 2024)
Manpower manages all the resources in the organization and helps the organization to grow and prosper. The purpose of the study is to examine determinants of the job satisfaction of stock brokers. Structural equation model using SMART PLS have been applied to examine significant relationship between exogenous and endogenous constructs. It is seen that Training and development; Rewards and recognition and Compensation packages (commission) significantly influences job satisfaction of stock brokers. The study is vital for the stock broking companies to manage their employees effectively and efficiently.
Keywords: Job satisfaction, Stock Brokers, Structural Equation Model, SEM